DESCRIPTION OF THE SANITATION KARANG ASEM STASION IN BANYUWANGI 2017 - Sari, Apik Mila; Puspikawati, Septa Indra; Islamiyah, Khofifatul; Ardiasnyas, Rizky Bagas; Putri, Fika Ardiana (Tadulako University, 2018)
Background & Purpose: Stations are one of the public places that have sanitation facilities and enable environmental pollution and diseases including diarrhea, dysentery, typhus, malaria and filiarisis. The aim of finding out the sanitation conditions at Station Karang Asem in Banyuwagi. Material and Methods: this study is an observational study conducted through a sheet of instrument that has been made based on applicable laws and interview sheets. The assessment instrument consists of 3 main variables that are used as the foundation in the assessment including the main building variables, sanitation facilities and supporting facilities at the station. of the 3 variables there are sub-variables and also sub-variables used as ratings. Assessment is done by looking at the total final score of the sum of 3 variable scores. Results: The total score of the main building variable 140 means fulfilling 100% sub-variable requirements, 77 sanitation facilities means fulfilling 50% of the assessment requirements of sub-variables and supporting facilities 97.5 means meeting the 21.5% assessment requirements of sub-variables. The total score of Karang Asem station sanitation is so that station x sanitation is 314.5. Which means in the Good category. Conclusion: Karang Asem Station in Banyuwangi has a Good category in station sanitation assessments, although there still needs to be an increase especially in its sanitation facilities.Keywords: station, sanitation, public place.